Frame Stability of Tunnel‐Structured Cryptomelane Nanofibers: The Role of Tunnel Cations. Issue 28 (25th July 2013) - Gao, Tao; Norby, Poul
Abstract: The role of tunnel K + ions on the growth and stability of tunnel‐structured cryptomelane‐type MnO2 nanofibers (denoted as cryptomelane nanofibers hereafter) has been discussed by means of X‐ray diffraction and electron microscopy. Cryptomelane nanofibers with typical diameters of 20–80 nm and lengths of 1–6 μm have been synthesized by means of a simple hydrothermal reaction of KMnO4 and MnSO4 aqueous solutions at 140 °C. The growth of cryptomelane nanofibers under hydrothermal conditions follows a dissolution–recrystallization process and involves a morphological transformation from a layered precursor to the tunnel‐structured cryptomelane, in which the K + ions play important roles in templating and stabilizing the tunneled framework. The presence of tunnel K + ions also enhances the frame stability of the cryptomelane nanofibers at elevated temperatures. The formation of a layered K x Mn2 O4 ( x ≈ 0.26) with a hexagonal phase structure has been observed at about 900 °C. The transformation from tunneled cryptomelane to layered K x Mn2 O4 also follows the dissolution–recrystallization growth mechanism, in which the diffusion of K + ions at high temperatures represents a critical process. The topological correlation between the tunneled and layered MnO2 materials might provide useful information for the synthesis of MnO2 nanomaterials with controlled microstructures for different applications. Abstract : The frame stability of tunneled or layered MnO2 materials is strongly correlated to their stabilizing cations.